Taxonomy of Kermes greeni Bodenheimer (Hemiptera: Coccoidea: Kermesidae) with a new synonymy - Spodek, Malkie; Ben-Dov, Yair; Protasov, Alex (Zootaxa, 2012)
The first-instar nymph and adult female of Kermes greeni Bodenheimer, 1931 are redescribed and a lectotype is designated. Kermes palestiniensis Balachowsky, 1953 is synonymized with K. greeni. This synonymy is based on a study of the type material of K. greeni and K. palestiniensis, as well as on fresh, topotypic material collected from Quercus calliprinos Webb in Israel.